Influence of Hyaluronic Acid Transitions in Tumor Microenvironment on Glioblastoma Malignancy and Invasive Behavior - Chen, Jee-Wei E.; Pedron, Sara; Shyu, Peter; Hu, Yuhang; Sarkaria, Jann N.; Harley, Brendan A. C. (Frontiers in Materials, 2018)
The extracellular matrix (ECM) is critical in tumor growth and invasive potential of cancer cells. In glioblastoma tumors, some components of the native brain ECM such as hyaluronic acid (HA) have been suggested as key regulators of processes associated with poor patient outlook such as invasion and therapeutic resistance. Given the importance of cell-mediated remodeling during invasion, it is likely that the molecular weight of available HA polymer may strongly influence GBM progression. Biomaterial platforms therefore provide a unique opportunity to systematically examine the influence of the molecular weight distribution of HA on GBM cell activity. Here we report the relationship between the molecular weight of matrix-bound HA within a methacrylamide-functionalized gelatin (GelMA) hydrogel, the invasive phenotype of a patient-derived xenograft GBM population that exhibits significant in vivo invasivity, and the local production of soluble HA during GBM cell invasion. Hyaluronic acid of different molecular weights spanning a range associated with cell-mediated remodeling (10, 60, and 500 kDa) was photopolymerized into GelMA hydrogels, with cell activity compared to GelMA only conditions (-HA). Polymerization conditions were tuned to create a homologous series of GelMA hydrogels with conserved poroelastic properties (i.e. shear modulus, Poisson’s ratio, and diffusivity). GBM migration was strongly influenced by HA molecular weight; while markers associated with active remodeling of HA (hyaluronan synthase and hyaluronidase) were found to be uninfluenced. These results provide new information regarding the importance of local hyaluronic acid content on the invasive phenotype of GBM.